A review on flexible wearables – Recent developments in non-invasive continuous health monitoring - Kazanskiy, Nikolay L.; Khonina, Svetlana N.; Butt, Muhammad A. (Sensors and actuators. A. Physical., 2024)
Wearable sensors hold profound significance in our increasingly interconnected world, revolutionizing the way we monitor and manage our health, daily activities, and environments. These compact, unobtrusive tools have transcended the realm of mere gadgets to become indispensable tools for individuals and healthcare professionals alike. By continuously collecting data on vital signs, physical activity, sleep patterns, and more, wearables empower users to gain valuable insights into their well-being, facilitating proactive health management. Beyond preventive medicine, wearables find applications in diverse fields, from sports performance optimization to industrial safety monitoring, making them catalysts for transformative change in the way we live, work, and thrive. As technology continues to advance, the significance of wearables in enhancing our lives and pushing the boundaries of knowledge will only continue to grow. In this review, we focused on the recent advances in the field of wearables for continuous non-invasive monitoring of cardiovascular, body temperature and blood glucose. These sensors are commonly incorporated into garments or stylish accessories such as watches, allowing individuals to monitor different facets of their health, including metabolic processes and vital signs. In premise, the worldwide wearables market is undergoing substantial growth propelled by technological advancements, expanding applications, and the need for inventive preventive healthcare solutions. Despite existing challenges, the industry is well-positioned for ongoing expansion as it tackles these issues and pushes the frontiers of wearable technology. [Display omitted] •This review discusses the novel and most recent developments on continuous non-invasive wearable sensors.•Applications of wearable sensors for cardiovascular, temperature and blood glucose monitoring are presented.•Challenges and possible solutions associated with the wide availability of wearables were discussed.